Enactment, provision, norm: reflections on the normativeness of provisions regulating the process of legislation - Grabowski, Paweł (Investigationes Linguisticae, 2009)
One of the crucial questions considered within the theory of law is the problem of sources of law (fontes iuris oriundi), that is, generally speaking, the ways in which the law is created. Nowadays decisively the most fundamental form of creation of law is the act of legislative understood as a conventional act of a competent public organ performed in accordance with the provisions regulating the process of establishing law. Considering this problem one may give two types of answers found in legal theory papers. Some scholars maintain that those provisions do not have normative character, pointing out that the norms of conduct are not the only basic units of law. According to the second position, provisions regulating the process of legislation do have normative character. This kind of view is represented probably in the most sophisticated form by Zygmunt Ziembiński, who holds that these provisions express a kind of a norm of conduct, namely power conferring norm (norm of a legislative competence), being a type of norm of competence, that is norm granting some competences to perform a definite conventional act. The purpose of my paper is to present both standpoints showing the examples of their most representative supporters. Furthermore, I will try to formulate my own solution to the problem. The concepts of Czesław Znamierowski, Herbert L. A. Hart, Alf Ross and Zygmunt Ziembiński will be presented.